AN ANALYSIS OF ENGLISH SPOKEN LEARNING DIFFICULTIES OF THE FOURTH SEMESTER STUDENTS AT ENGLISH EDUCATION STUDY PROGRAM OF BATANGHARI UNIVERSITY IN ACADEMIC YEAR 2016/2017 - Ade Pirma Bahri; Wennyta Wennyta; Nurul Fitri (Universitas Batanghari Jambi, 2017)
English Learning is a process where a learner expanding his/her knowledge about English and its implementation. Speaking Difficulty is the inhibition that a learner used to face when they learn to use language orally. The purpose of conducting this research is to know about the difficulties that the students have in English spoken learning. Design of this research uses Qualitative research. The subject of the research is the fourth semester students of Batanghari University in academic year 2016/2017.Keyword: English Learning, Speaking Difficulty